China's rise and the Arctic region up to 2049 – three scenarios for regional futures in an era of climate change and power transition. Issue 1 (2nd January 2022) - Kauppila, Liisa; Kopra, Sanna
ABSTRACT: Although China has emerged as an increasingly influential global actor over recent decades, it is unclear whether a more fundamental transformation is shaking processes of regionalisation in this context. Our scenario-based case study considers the spatial reconfiguration of the rapidly globalising Arctic with varying degrees of Chinese engagement. More specifically, we examine alternative and transformational configurations of the Arctic in 2049, and ponder upon the plausibility of the hypothesised changes in light of three schools of thought on International Relations – realism, liberal institutionalism and relationalism. Hence, we explore how the rise of China could potentially alter the regional dynamics and whether, consequently, regions should be rethought both empirically and theoretically. We conclude that pluralistic discussion on the multiple regional outcomes is a necessary precondition for achieving a balanced and democratic future in the Arctic and beyond.